2021
DOI: 10.12968/hmed.2020.0659
|View full text |Cite
|
Sign up to set email alerts
|

Rare but relevant: a systematic review of stercoral perforation

Abstract: Background/Aims Knowledge of the aetiologies of large bowel perforation are fundamental to its management. Stercoral perforation is a rare cause associated with high mortality. Owing to the paucity of coverage of this condition in the literature, this review raises awareness of stercoral perforation among clinicians. Method A literature search of PubMed, Embase, MEDLINE, CINAHL, Ovid and Cochrane was performed. Key search terms included ‘stercoral, perforation’, ‘perforated’, ‘perforat*’ and ‘stercoral perfora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…They are associated with stercoral colitis, lower gastrointestinal (GI) bleed, perforation, and peritonitis. 2 Perforated stercoral ulcers were reported to have a mortality between 30 and 60%, with recent literature reporting lower rates of mortality at 17%. 2 Clinical suspicion and imaging are essential for early diagnosis.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…They are associated with stercoral colitis, lower gastrointestinal (GI) bleed, perforation, and peritonitis. 2 Perforated stercoral ulcers were reported to have a mortality between 30 and 60%, with recent literature reporting lower rates of mortality at 17%. 2 Clinical suspicion and imaging are essential for early diagnosis.…”
Section: Articlementioning
confidence: 99%
“…2 Perforated stercoral ulcers were reported to have a mortality between 30 and 60%, with recent literature reporting lower rates of mortality at 17%. 2 Clinical suspicion and imaging are essential for early diagnosis. Imaging depicts fecal impaction as well as signs of focal colonic inflammation such as thickening and fast stranding.…”
mentioning
confidence: 99%
“…2 It is associated with tricyclic antidepressants and long-term opiate use, with one-fifth of patients with stercoral perforation having opioid use disorder. 4 There is a high rate of concomitant comorbidities, such as diabetes mellitus, hypertension, malignancy, hypothyroidism, depression, dementia, and orthopedic injury or cerebrovascular accident, leaving patients bedridden. 5 Stercoral colitis rarely leads to perforation, with 0.7% of CT reports with fecal impaction or stercoral colitis having perforation.…”
Section: Introductionmentioning
confidence: 99%
“…Stercoral perforation is a rare but life-threatening condition that is increasingly being recognised as a real entity associated with severe constipation. Systematic reviews thus far have identified approximately two hundred patients diagnosed with stercoral perforation, although it is likely that it has been significantly under-reported [ 1 , 2 ]. Although the mechanism is not fully understood, it is thought that impacted faecalomas may cause local pressure with subsequent ischaemia and necrosis of the colonic wall, leading to a stercoral ulcer or perforation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%